Building development studies for the new millennium - Baud, Isa; Basile, Elisabetta (London Palgrave Macmillan, 2019)
This book brings together multiple critical assessments of the current state and future visions of global development studies. It examines how the field engages with new paradigms and narratives, methodologies and scientific impact, and perspectives from the Global South. The authors focus on social and democratic transformation, inclusive development and global environmental issues, and implications for research practices. Leading academics provide an excellent overview of recent insights for post-graduate students and scholars in these research areas. Isa Baud is Emeritus Professor of International Development Studies at the University of Amsterdam, the Netherlands. Elisabetta Basile is Professor of Development Economics at the University of Rome La Sapienza, Italy. Tiina Kontinen is Senior Lecturer at the Master Degree Programme in Development and International Cooperation, University of Jyväskylä, Finland. Susanne von Itter is Executive Director of EADI, Germany.
Keywords: Desarrollo económico -- Estudios; Universidades -- Investigación